TRAIN STUDENTS' CREATIVITY WITH PAPER FOLDING MEDIA USING ORIGAMI PAPER" - Mohamad Shafri Wawointana; Dea; Fuji Pratiwi Y. Laiya; Ulva Fionita I. Palo; Abdul Rahmat; Abd. Hamid Isa (Scholar Express Journal, 2022)
Creativity is someone's ability to produce something new. Where it can be in the form of ideas or products or new works, which are different from what existed before, or combine the two into something different. The purpose of this study was to find out and analyze the creativity of students using origami paper. The results of the study stated that learning using origami paper media can have an influence on the development of children's creativity so that it makes children more happy in terms of folding origami, the better in terms of developing their creativity. The conclusion from this article is that children's creativity using origami paper media can be an alternative means of training children's creativity, as seen from the enthusiasm of children to learn to try to make a shape from this one to that one and try again if they fail in folding paper. The Origami
Keywords: Creativity; Origami Paper